Gut microbiota remodeling exacerbates neuroinflammation and cognitive dysfunction via the microbiota-gut-brain axis in prenatal VPA-exposed C57BL/6 mice offspring - Liu, Zhaoming; Wu, Caixia; Sun, Zhaojian; Lin, Zuoxian; Sun, Yirong; Amjad, Nouman; Majid, Muhammad; Basnet, Rajesh; Li, Zhiyuan (Frontiers in Immunology, 2025)
IntroductionPrenatal exposure to valproic acid (VPA) is a recognized risk factor for autism spectrum disorder (ASD)-like phenotypes, yet the mechanisms linking gut microbiota dysbiosis to neurodevelopmental impairments remain poorly understood. Emerging evidence implicates the microbiota-gut-brain axis as a critical mediator of neuroinflammation and cognitive deficits, but causal pathways in VPA-induced ASD models require systematic exploration. This study investigates how prenatal VPA exposure reshapes gut microbiota composition, exacerbates neuroinflammatory responses, and drives cognitive dysfunction through the microbiota-gut-brain axis in C57BL/6 mouse offspring.MethodsPrenatal VPA-exposed and control offspring underwent behavioral assessments (open field, three-chamber social interaction, marble-burying, and Morris water maze tests). Neuroinflammatory cytokines (IL-1β, IL-6, TNF-α, IL-10), oxidative stress markers (GSH, SOD, MDA), and microglial activation (Iba1 immunofluorescence) were quantified. Gut microbiota profiles were analyzed via 16S rRNA sequencing, with functional pathway predictions using PICRUSt2 and KEGG databases.ResultsVPA-exposed mice exhibited ASD-like behaviors, including social deficits, repetitive stereotypic actions, and impaired spatial memory. Neuroinflammation was marked by upregulated pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and microglial hyperactivation, alongside suppressed antioxidant systems (GSH, SOD). Gut microbiota analysis revealed dysbiosis characterized by reduced Bacteroidia and enriched Clostridia, with diminished short-chain fatty acid (SCFA)-producing taxa (e.g., Oscillibacter). Co-occurrence networks highlighted disrupted microbial interactions, while functional profiling indicated impaired carbohydrate metabolism and elevated neurotoxic pathway activity.DiscussionPrenatal VPA exposure induces gut microbiota remodeling that exacerbates neuroinflammation and cognitive dysfunction via the microbiota-gut-brain axis. This study provides evidence for linkages between taxonomic and metabolic gut dysbiosis and ASD-like pathophysiology, underscoring the therapeutic potential of microbiota-targeted interventions for neurodevelopmental disorders.